The problem of the status of mediatization theory in communication studies - Kirtiklis, Kęstas (Information & Media, 2015)
The article deals with the mediatization theory, particularly with the problem of its status in the communication theory and research. The article discusses the relationship of the mediatization theory with the traditional mass communication research and the classical media theory, as well as the main currents of mediatization theory – (1) institutional and (2) social-constructivist – and their conceptions of mediatization, based, respectively, on the notions of (1) media logic and (2) metaprocess. The article suggests that contemporary forms of the mediatization theory generally should be considered as an aprioristic holistic theory of social explanation proposing a methodological approach to the research of interaction between the media and society rather than an empirically based description of the social reality.